Analysis of Determinants of the Rupiah Exchange Rate (Exchange Rate) against the US Dollar in 2016: Q1-2023: Q4 - Silalahi, Clinton P.; Rotinsulu, Tri O.; Maramis, Mauna Th. B. (Formosa Journal of Applied Sciences, 2024)
In foreign trade, exchange rates are one of the big factors that make a big difference. And although each country has its own currency, they all have different monetary values. To show how much one country's currency is worth compared to another country's currency, we need a measure called the exchange rate. The aim of this research is to find out how the exchange rate is related to things such as the amount of money in circulation, non-oil and gas exports, the balance of payments, and Indonesia's benchmark interest rate. A multiple regression analysis model was used to conduct the research. This research shows that the IDR/USD Exchange Rate is closely related to Indonesia's Balance of Payments, Money Supply (M2), Non-Oil and Gas Exports, and Reference Interest Rates. This relationship is real and good.